2005
DOI: 10.2190/6pcm-447v-wf7b-qeuf
|View full text |Cite
|
Sign up to set email alerts
|

Solving Problems Reductively

Abstract: Solving problems by reduction is an important issue in mathematics and science education in general (both in high school and in college or university) and particularly in computer science education. Developing reductive thinking patterns is an important goal in any scientific discipline, yet reduction is not an easy subject to cope with. Still, the use of reduction usually is insufficiently reflected in high school mathematics and science programs. Even in academic computer science programs the concept of redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
2

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Reductive thinking, as demonstrated by high school students' solutions to questions dealing with computational models, was discussed in Armoni, Gal-Ezer, and Tirosh (2005). The findings showed that many students preferred direct, nonreductive solutions, even in cases in which reductive solutions could have significantly decreased the complexity of the solution.…”
Section: Reduction As a Habit Of Mind In Csmentioning
confidence: 99%
“…Reductive thinking, as demonstrated by high school students' solutions to questions dealing with computational models, was discussed in Armoni, Gal-Ezer, and Tirosh (2005). The findings showed that many students preferred direct, nonreductive solutions, even in cases in which reductive solutions could have significantly decreased the complexity of the solution.…”
Section: Reduction As a Habit Of Mind In Csmentioning
confidence: 99%
“…The first study examined reductive thinking of high school students in the context of computational model problems [Armoni et al 2005]. The findings showed that many students preferred direct, nonreductive solutions, even in cases in which reductive solutions could have significantly decreased the complexity of the solution.…”
Section: Relevant Workmentioning
confidence: 99%
“…The first study examined reductive thinking of high school students in the context of computational model problems [3]. The findings showed that many students preferred direct, non-reductive solutions, even in cases in which reductive solutions could have significantly decreased the complexity of the solution.…”
Section: Relevant Workmentioning
confidence: 99%